Transform Nutrition West Africa: Looking back to move forward - Verstraeten, Roosmarijn (International Food Policy Research Institute, 2021)
Four years ago, a group of senior scientists from the International Food Research Institute (IFPRI) and the Institute of Development Studies (IDS), along with representatives from the Bill & Melinda Gates Foundation (BMGF) and the African Nutrition Leadership Programme (ANLP), came together to address malnutrition in West Africa through the Transform Nutrition West Africa (TNWA) project. When the project was initiated in 2017, the region had made only limited and uneven progress in reducing high levels of malnutrition: wasting and stunting were prevalent among children and half of the women of reproductive age were anemic, even as maternal overweight and obesity were becoming increasingly common. In response, TNWA was developed as a bilingual regional knowledge platform for informing and supporting decision-making on maternal, infant, and young child nutrition (MIYCN).